1988
DOI: 10.2307/1130668
|View full text |Cite
|
Sign up to set email alerts
|

Newborn Response to Auditory Stimulus Discrepancy

Abstract: Newborns were assessed for their recovery of head turning toward laterally presented auditory stimuli (titi) that varied from a familiar standard on 1 of 5 levels of fundamental frequency. Following habituation to repeated standard trials, newborns recovered to 14% and 21%, but not to 0%, 7%, or 28% discrepancies, indicating that recovery was a quadratic function of the degree of stimulus-schema discrepancy. Moreover, newborns reliably turned away from the standard stimulus during posthabituation no-change con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…All of these infants, including those in the glucose group, displayed clear recovery of turning toward a novel word after being re-exposed to the previously learned word, assuring that a lack of recovery to the prior stimulus could not be accounted for by fatigue, sleep or other reason. Because of previous evidence that such recovery following a delay can be accounted for most convincingly by an information processing interpretation that posits a mental representation of the stimulus (Rovee-Collier et al, 1982;Sokolof, 1963;Swain et al, 1993;Tarquinio et al, 1990;Thompson & Spencer, 1966;Weiss et al, 1988;Zelazo et al, 1991), this is good evidence that newborn infant memory for spoken words can be enhanced by a glucose feeding.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…All of these infants, including those in the glucose group, displayed clear recovery of turning toward a novel word after being re-exposed to the previously learned word, assuring that a lack of recovery to the prior stimulus could not be accounted for by fatigue, sleep or other reason. Because of previous evidence that such recovery following a delay can be accounted for most convincingly by an information processing interpretation that posits a mental representation of the stimulus (Rovee-Collier et al, 1982;Sokolof, 1963;Swain et al, 1993;Tarquinio et al, 1990;Thompson & Spencer, 1966;Weiss et al, 1988;Zelazo et al, 1991), this is good evidence that newborn infant memory for spoken words can be enhanced by a glucose feeding.…”
Section: Discussionmentioning
confidence: 90%
“…The primary outcome measure was the percentage of trials in which the infant turned his/her head towards the stimulus (percent head turns towards) during the first six trials (or less if the infant reached criterion for orientation earlier) of the recovery phase as in previous studies (Weiss, Zelazo, & Swain, 1988;Zelazo et al, 1987). Our hypothesis predicts that the percent head turns towards the sound should be lower in infants who received glucose than in those who received water.…”
Section: Outcome Measuresmentioning
confidence: 93%
“…The neonatal research reveals that the capacity for schema formation and stimulus-schema discrepancy are inherent features of the human cognitive makeup that are fully functional at birth, but it also lays bare a puzzling paradox. Why is it that neonates in the Weiss et al (1988) study displayed a low level of responsiveness, even avoidance, to the extremely discrepant stimuli but showed full recovery to a subsequent novel sound that had even less in common with the standard stimulus? The paradox was resolved by postulating a two-process model: Stimulus-schema comparisons were hypothesized to be context dependent, whereas novel stimuli were regarded as context independent.…”
Section: A Two-process Phenomenonmentioning
confidence: 99%
“…Researchers attempted to determine whether the effect of stimulus discrepancy from an experimentally introduced standard (the schema) was curvilinear as claimed by earlier theorists, or linear as some early research seemed to indicate (e.g., Cohen et al, 1971;Fantz, 1964;Melson & McCall, 1970;Welch, 1974). Results over multiple studies more consistently supported a curvilinear effect (e.g., Hopkins et al, 1976, Kinney & Kagan, 1976McCall & Kagan, 1967;Super et al, 1972;Weiss et al, 1988). Indeed, McCall et al (1977 reported 25 independent groups of infants that displayed the inverted U discrepancy effect.…”
Section: Infant Research On Stimulus-schema Discrepancymentioning
confidence: 99%
See 1 more Smart Citation